Sexual and Reproductive Health Sexual and Reproductive Health Knowledge, Attitude and Practice SURVEY and Service Quality Assessment in Tirana - Spahiu, Miranda; Dhamo, Eris; Hallkaj, Elda (European Scientific Journal, ESJ, 2016)
Sexual and reproductive health services in Albania are based on a positive history of services quality and access. However, in the context of the past decades changes in the social and population perspective, these services are faced with the challenge to meet increasing and evolving demands from girls and women. The data available are scare to portray a good picture of the knowledge, attitude practice and other dimensions of access and quality of sexual and reproductive services from the viewpoint of girls and women. The findings introduced in this article present an attempt to add on the evidence, with the target of Tirana, being the most populated city. The methodology used in this research is composed by two components: the quantitative KAP survey, and the qualitative assessment of the services’ access and quality. The first instrument is tested and has passed the necessary reliability and validity tests and the second instrument is a focus group with girls and women. Both data are analysed with respective software. The respondents reported low level of knowledge on contraception methods, risk factors for cervical cancer, and signs of breast cancer. They accept that practices in terms of modern contraception are not frequent, similar are the prevention measures or testing for cervical cancer, IST/HIV. The study identifies that many barriers remain strong for girls and women in Tirana to access quality services.